Fetus, Fasting, and Festival: The Persistent Effects of In Utero Social Shocks - Xi Chen (Kerman University of Medical Sciences, 2014)
The Fetal Origins Hypothesis (FOH), put forward in the epidemiological literature and later flourished in the economics literature, suggests that the time in utero is a critical period for human development. However, much attention has been paid to the consequences of fetal exposures to more extreme natural shocks, while less is known about fetal exposures to milder but more commonly experienced social shocks. Using two examples of under-nutrition due to mild social shocks, i.e. Ramadan fasting and festival overspending, this paper summarizes our current knowledge, especially the contribution from economics, and key challenges in exploring fetal exposures to milder social shocks. I also discuss the salient added value of identifying milder versus more extreme fetal shocks. Finally, implications are drawn on individual decisions and public policy to improve children's well-being before they are born or even before their mothers realize that they are pregnant.